2016
DOI: 10.1515/intag-2015-0078
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of tocopherols during rapeseed storage in simulated conditions of industrial silos

Abstract: A b s t r a c t. The investigations consisted in laboratory simulation of conditions prevailing in the real ecosystem in an industrial rapeseed storage facility. The aim of the study was to assess the impact of temperature, moisture, and static pressure on degradation of tocopherols contained in rapeseed. Rapeseed varieties with high oil content were analysed in the investigations. Samples of seeds with 7, 10, 13, and 16% moisture levels were stored at a temperature of 25, 30, and 35°C in specially designed ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…in black‐seeded mustard seeds was also markedly lower (39.4 mg kg −1 oil for the α‐T homologue and 414 mg kg −1 oil for the β + γ‐T homologue) than in white mustard seeds. The total tocopherol content of oil produced from the tested white mustard seeds was also much greater than in the oil from seeds of either black‐seeded and yellow‐seeded rape . However, the ratios of individual tocopherol homologues were different in rapeseed oil, with the γ‐T homologue accounting for 57–62% total tocopherol content, while the α‐T homologue accounted for 36–41% .…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…in black‐seeded mustard seeds was also markedly lower (39.4 mg kg −1 oil for the α‐T homologue and 414 mg kg −1 oil for the β + γ‐T homologue) than in white mustard seeds. The total tocopherol content of oil produced from the tested white mustard seeds was also much greater than in the oil from seeds of either black‐seeded and yellow‐seeded rape . However, the ratios of individual tocopherol homologues were different in rapeseed oil, with the γ‐T homologue accounting for 57–62% total tocopherol content, while the α‐T homologue accounted for 36–41% .…”
Section: Resultsmentioning
confidence: 84%
“…The flow rate was 1.0 mL min −1 . The fluorometric detector (Waters 474) worked at an excitation wavelength of 295 nm and an emission wavelength of 330 nm . The tocopherols (α‐T, β‐T, γ‐T, δ‐T) were identified by comparing retention times, while the concentrations were calculated by comparing the area values with those of external standard tocopherols (Merck, Darmstadt, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, it is the increase in humidity from 7 to 9% that causes an eight-fold increase in the intensity of the processes. What is more, a study by Gawrysiak-Witulska et al (2016) on the losses of the total tocopherol content, showed that moisture had the greatest impact. This was followed by temperature, while pressure had a slight effect.…”
Section: Resultsmentioning
confidence: 98%
“…The seed was then transferred into white polypropylene containers (500 mL) with a screw lid, containing the same headspace volume in each, and placed into containers in the respective treatment conditions (Table ). Moisture was kept to a minimum during the study since seed with moisture levels above 8% are rejected by seed processors, due to the risk of seed spoilage, and spontaneous combustion with silo storage of seed with high moisture . This was achieved by the use of dessicant sachets in all seed samples throughout storage, and the testing of seed moisture at each time of analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have investigated the effects of: Short‐term storage and excessive heating, and varied temperatures with high moisture content, on phytosterol composition in vegetable oils. Tocopherol composition during seed storage has been investigated relative to temperature and moisture extremes, and in oil, relative to temperature and oxygen exposure . Similarly, increases in oxidative stability and the subsequent losses in tocopherols were observed in rapeseed stored in varied conditions over 24 months, with the greatest losses occurring at higher storage temperatures .…”
Section: Introductionmentioning
confidence: 99%